Gastrointestinal manifestations of neuroendocrine tumours: their investigation and management. Issue 1102 (9th June 2017) - Sagar, Vandana M; Cooper, Sheldon C; Johnson, Jill; Shetty, Shishir; Shah, Tahir
ABSTRACT: The incidence of neuroendocrine tumours (NETs) is on the rise in the UK. Patients with NETs need to be managed by a team of clinical specialties. There are a number of challenging gastrointestinal (GI) manifestations related to NETs that can occur in these patients, but a limited literature base exists to guide clinicians. Whilst life expectancy can be several years for patients with NETs, the GI symptoms can have a significant impact on their quality of life. It is therefore imperative to be familiar with the common GI manifestations associated with NETs, so symptoms can be appropriately managed with an overall aim of restoring the patient's quality of life.